Cardiovascular Fitness in College Students: Role of Blood Type and Somatotype - Arimbi, Arimbi; Usman, Arifuddin; Sarifin, Sarifin; Arfanda, Poppy Elisano; Anggraeni. M, Andi Sri Dewi (ETDC: Indonesian Journal of Research and Educational Review, 2025)
This study intends to analyze the differences in cardiovascular endurance based on blood type and somatotype in college students. The study included 213 participants, consisting of 68 college students with blood type A, 68 with blood type B, 68 with blood type O, and 9 with blood type AB from the Faculty of Sport Science at Universitas Negeri Makassar. Cardiovascular endurance was assessed using the Multistage Fitness Test (MFT), blood type identification from the respondent's blood type card, and a somatotype assessment based on an anthropometric assessment. The investigation revealed that blood type O had stronger cardiovascular endurance than others, with a higher proportion of both satisfactory and fair categories. In contrast, blood type AB was associated with less endurance, with a large proportion in poor and destitute categories. Mesomorphs outperformed endomorphs and ectomorphs in terms of cardiovascular performance, which supports the theory that an individual's body type determines aerobic abilities. Furthermore, the chi-square test revealed a significant correlation between blood type and cardiovascular endurance (p < 0.05). This study considerably improves our understanding of how blood type and somatotype combinations affect athlete performance across various sports. This study recommends the integration of biometric and anthropometric data in athlete selection and development strategies to achieve optimal results.